Les termes juridiques français et slovaques du point de vue de leur formation et de leur motivation - Kupčihová, Katarína (Verbum – Analecta Neolatina, 2006)
The paper focuses on a highly specific lexical field of juridical terminology. The analysis of the word-formation process, which is generally called compounding, takes into consideration two types of coining new words in French, "proper" and "improper" compounding. These two types are compared to their Slovak equivalents in order to investigate differences in their motivation.